Gender Specific Mutation Incidence and Survival Associations in Clear Cell Renal Cell Carcinoma (CCRCC). - Christopher J Ricketts; W Marston Linehan (PLoS ONE)
Renal cell carcinoma (RCC) is diagnosed in >200,000 individuals worldwide each year, accounting for ~2% of all cancers, but the spread of this disease amongst genders is distinctly uneven. In the U.S. the male:female incidence ratio is approximately 2:1. A potential hypothesis is mutation spectra may differ between tumors dependent upon the gender of the patient, such as mutations of X chromosome encoded genes being more prevalent in male-derived tumors. Combined analysis of three recent large-scale clear cell renal cell carcinoma (CCRCC) mutation sequencing projects identified a significantly increased mutation frequency of PBRM1 and the X chromosome encoded KDM5C in tumors from male patients and BAP1 in tumors from female patients. Mutation of BAP1 had previously been significantly associated with poorer overall survival; however, when stratified by gender, mutation of BAP1 only significantly affected overall survival in female patients. Mutation of chromatin remodeling genes alters gene regulation, but the overall effect of these alterations may also be modified by the presence of other gender specific factors. Thus, the combination of gender and mutation of a specific gene, such as BAP1, may have implications not only for prognosis but also for understanding the role of chromatin remodeling gene mutations in kidney cancer progression.